The evolving definition of quality: how teacher experience and subject domain shape perceptions of instructional materials - Garay Abad, Lola; Hattie, John (Frontiers in Education, 2025)
IntroductionDespite substantial global investment in curricular resources, surprisingly little empirical research has explored how teachers themselves define and evaluate the quality of instructional materials, particularly as these perceptions evolve across different stages of the teaching career. This study examined how teachers’ approaches to evaluating instructional material quality evolve across career stages.MethodsWe surveyed 2,102 educators from Germany, Austria, and Switzerland, all active users of the eduki platform. Through exploratory factor analysis and multivariate analysis of variance (MANOVA), we identified three distinct response patterns in how teachers evaluate materials: teacher perceptions of peer-created material quality, pedagogical and structural characteristics of high-quality materials, and teacher-centric considerations and practical benefits.ResultsTeachers’ priorities across these evaluation approaches vary significantly with experience. The overall MANOVA was statistically significant (Wilks’ Lambda = 0.89, F(81, 4,476) = 1.97, p < 0.001). Early-career teachers emphasize peer-created materials for lesson delivery (M = 4.34, SD = 0.69) and professional development (M = 3.88, SD = 0.87), along with stimulating content (M = 4.16, SD = 0.95) and curriculum compliance (M = 3.85, SD = 0.96). In contrast, experienced teachers prioritize practical benefits such as ease of use (M = 3.84, SD = 0.93), technology integration (M = 3.29, SD = 0.94), support for diverse learning needs (M = 3.85, SD = 0.88), and inclusion of current research (M = 3.34, SD = 0.90), with effect sizes ranging from small to moderate (d = −0.33 to 0.54). The greatest differences were observed between early-career and experienced teachers.DiscussionThese findings indicate that quality evaluation is a developmental process that evolves with teaching expertise. We propose a career-responsive approach to material development with implications for content design, professional development, and platform personalization.